Regional public goods in official development assistance - Ferroni, Marco (IDB WashingtonUS, 2001)
Reviews the demand, and the case, for regional public goods in the light of growing integration. Reports on the response of certain international organizations and the system of official development assistance to perceived growth in the demand for these goods. Analyzes the challenges of financing regional public goods. Explains lending practices and the need for grants, and suggests some scope for innovation in the financing of regional public goods.